Business Strategy and Environmental Practices: evidences on the sugar-alcohol sector - Machado, André Gustavo Carvalho; Silva, Josuéliton da Costa (Review of Business Management, 2010)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> This article aims at analyzing how companies that belong to the sugar-alcohol sector are dealing with environmental management under a strategic perspective. The research strategy chosen was the study of multiple cases undertaken in eight companies located in the states of Pernambuco and Paraíba. The main data gathering technique was the semi-structured interview. The analysis of data took place in two stages: individual analysis and crossed analysis of the cases. The results showed evidence that clients, society, competitors and governments are the main actors to influence companies, in the sense of making them rethink the consequences of their decisions under an environmental perspective. The formation of the strategy through the tool of planning was the most evidenced in the research. A theme that draws attention is that it was not found, in any of the companies studied, effective return measures for the environmental investments. Despite the commitment of the high administration with environmental matters supporting efforts in that direction, the environmental dimension seems to be relegated to specific functional levels, in a way that the alignment between operational and strategic issues is still incipient. Through the analysis of the main practices undertaken by the companies in the industrial sector, it is noticed that there still is a greater emphasis on corrective actions. However, there are growing efforts in favors of a pre-emptive behavior towards a strategic approach. Key words: <!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>Strategy. Environmental management. Sugar-alcohol sector.